2019
DOI: 10.1111/acem.13694
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of Gender Disparities in Pay Among Academic Emergency Medicine Physicians

Abstract: Objectives:The objective was to identify the effects of gender and other predictors of change in the salary of academic emergency physicians over a four sequential time period of survey administration, across a sample of physicians within different emergency departments (EDs) and within states representing the four main geographical regions of the United States.Methods: This was a successive cross-sectional observational study of EDs in the United States using an annual salary survey distributed to all Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 13 publications
(14 reference statements)
5
52
0
Order By: Relevance
“…Numerous studies, mostly from the United States and the United Kingdom, have shown a clear gender pay gap among phys icians. [7][8][9][10][11][12][13] This effect is seen in clinical, 14 research 15 and aca demic 16,17 environments. Inequities start at the early stages of a medical career, 18,19 deepen with time, 20 continue into retire ment 21 and affect lifetime wealth, 22 with estimates as high as $2.5 million over a 30year career.…”
Section: Is the Gender Pay Gap Real?mentioning
confidence: 94%
“…Numerous studies, mostly from the United States and the United Kingdom, have shown a clear gender pay gap among phys icians. [7][8][9][10][11][12][13] This effect is seen in clinical, 14 research 15 and aca demic 16,17 environments. Inequities start at the early stages of a medical career, 18,19 deepen with time, 20 continue into retire ment 21 and affect lifetime wealth, 22 with estimates as high as $2.5 million over a 30year career.…”
Section: Is the Gender Pay Gap Real?mentioning
confidence: 94%
“…Among physicians overall, sex differences in income persist even after adjustment for specialty choice, hours worked, years of experience, and family structure. 1 2 3 4 5 6 7 8 9 Among academic physicians, sex differences in income persist after adjustment for factors such as age, marital status, race, years of experience, specialty, work hours, research productivity, and faculty rank. 10 11 12 13 14 15 16 Differences in income are not supported by differences in clinical quality.…”
Section: Introductionmentioning
confidence: 99%
“…Most strikingly, even after adjusting for a comprehensive list of variables including race, region, rank, years of experience, clinical hours, core faculty status, administrative roles, board certification, and fellowship training, the mean salary for women is $19,418 less than men . This gender salary gap has notably remained stable over the past few years …”
mentioning
confidence: 99%